An analysis of the codes of good practice issued in terms of the Broad Based Black Economic Empowerment Act 53 of 2003 - Knoetze, Hyla Magdalena (University of the Free State, 2006)
BBBBBEE170 is an essential ingredient in facilitating the meaningful participation of blacks at all levels of the South African economy, in order to ensure sustainable socio-political and economic stability and the sustainability of the economic growth and development. BBBEE key principles • It is an ongoing process and not an event • It is a business imperative and an integral component of the company’s business strategy and is based on the core values of the organization • • It must result in meaningful and significant participation of blacks in the company and in the broader economy, through substantial changes in the racial composition of ownership, control, management structures and of skilled and specialist positions • It must lead to advantaged strategic position for the company, greater profitability, business growth and sustainable increase in stakeholder value • it is the responsibility of all management in the organisation.

Swart ekonomiese bemagtiging (hierna verwys “SEB”)171 ‘n belangrike bestanddeel in fasilitering van ‘n betekenisvolle deelname van swart mense op alle vlakke van die Suid-Afrikaanse ekonomie is, ten einde volhoubare sosiopolitieke en ekonomiese stabiliteit en volhoubare ekonomiese groei en ontwikkeling te verseker. SEB sleutelbeginsels SEB is ‘n deurlopende proses en nie ‘n eenmalige gebeurtenis nie. Dit is gebiedend noodsaaklik vir ‘n besigheid, ‘n integrale komponent van die besigheid se strategie en gebaseer op die kernwaardes van die maatskappy. Dit moet aanleiding gee tot betekenisvolle swart deelname aan die maatskappy en in die breër ekonomie, deur wesenlike verandering in die rassesamestelling van eienaarskap, beheer, bestuurstrukture en vaardigheids- of spesialis poste meebring. Dit moet aanleiding gee tot ‘n voordelige strategiese posisie vir die maatskappy, groter winsgewendheid, besigheidsgroei en volhoubare verhoging van waarde vir belanghebbendesDit is die verantwoordelikheid van alle bestuurslede in die organisasie.
Dissertation (LL.M. (Mercantile Law))--University of the Free State, 2007
Keywords: Employee empowerment -- South Africa; Business enterprises, Black -- South Africa; Affirmative action programs -- South Africa; Scorecard; Codes; Racism; African Apartheid; Black Economic Empowerment; BBBEE; Broad-Based; Transformation; Sector Charter